PENGARUH ENTREPRENEURIAL EDUCATION, PERSONALITY DAN SELF-EFFICACY TERHADAP MINAT BERWIRAUSAHA - Abdi, Anastasia Natali; Utami, Christina Whidya; Vidyanata, Deandra (Fakultas Ekonomi dan Bisnis, UNTAN, 2021)
ABSTRACTEntrepreneurship is one of the efforts to advance the economy in Indonesia. However, the phenomenon that occurs in this country is still low the number of entrepreneurs. According to Lutje and Franke's model (LFM), there are internal and external factors in fostering interest in entrepreneurship. Therefore, this research wants to determine how significant the internal and external factors toward the entrepreneurial intention. This research aims to find out and analyze the effect of entrepreneurial education, personality, and self-efficacy on entrepreneurial intention. There are four variables in this research, that is, entrepreneurial education (X1), personality (X2), self-efficacy (X3), and entrepreneurial intention (Y). The method in this research is a quantitative method by distributing an online questionnaire. The sample in this research is Universitas Ciputra students majoring in the 2017 batch of International Business Management who chose start-up guild with 152 respondents. This research indicates that entrepreneurial education and self-efficacy affect positive and significant entrepreneurial intention, whereas personality does not affect entrepreneurial intention. The conclusion is that entrepreneurial education provided by Universitas Ciputra has succeeded in increasing entrepreneurial intention, and self-efficacy is also able to encourage students in entrepreneurship. In contrast, student personality factors do not affect entrepreneurial intention.ABSTRAKBerwirausaha adalah salah satu upaya dalam memajukan ekonomi di Indonesia. Namun fenomena yang terjadi di negeri ini adalah masih rendahnya jumlah wirausahawan di Indonesia. Seorang wirausahawan harus di dorong oleh berbagai faktor agar memiliki minat berwirausaha sehingga dapat menjalankan bisnisnya. Menurut Luthje and Franke